2011
DOI: 10.1002/ajmg.b.31202
|View full text |Cite
|
Sign up to set email alerts
|

Exploring DRD4 and its interaction with SLC6A3 as possible risk factors for adult ADHD: A meta‐analysis in four European populations

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a common behavioral disorder affecting about 4-8% of children. ADHD persists into adulthood in around 65% of cases, either as the full condition or in partial remission with persistence of symptoms. Pharmacological, animal and molecular genetic studies support a role for genes of the dopaminergic system in ADHD due to its essential role in motor control, cognition, emotion, and reward. Based on these data, we analyzed two functional polymorphisms within the DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 83 publications
(103 reference statements)
0
19
0
1
Order By: Relevance
“…Here below we described candidate gene association studies (Table 1), 33, 34, 45, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65 pharmacogenetic (Table 2) 66, 67, 68 and biochemical (metabolomic) (Table 3) 46, 69, 70, 71, 72, 73, 74 studies for which it was possible to conduct meta-analysis. Moreover we described the studies for which the meta-analyses were not possible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here below we described candidate gene association studies (Table 1), 33, 34, 45, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65 pharmacogenetic (Table 2) 66, 67, 68 and biochemical (metabolomic) (Table 3) 46, 69, 70, 71, 72, 73, 74 studies for which it was possible to conduct meta-analysis. Moreover we described the studies for which the meta-analyses were not possible.…”
Section: Resultsmentioning
confidence: 99%
“…26, 28, 29, 76, 77 The current meta-analysis included six studies. 33, 53, 54, 57, 58, 60 Tovo-rodrigues et al 59 was excluded because insufficient data were reported. Also for this polymorphism different calculations were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Indo-Caucasoid ADHD probands, we have also observed significant association of the higher repeats [5]. Another repeat variant rs4646984, located about 1.2 kb upstream of the initiation codon and affecting transcriptional activity of the promoter [14], showed nominal association of the duplicated allele in Caucasian population from Norway, Spain [55], and USA [14, 56]. On the other hand, haplotypes containing the single repeat allele have shown higher frequency in Caucasian ADHD probands from Hungary [13].…”
Section: Discussionmentioning
confidence: 96%
“…The long version of the tandem duplication has been associated with attention deficit hyperactivity disorder (ADHD) and schizophrenia, conditions that are sometimes characterized by impulsivity [26], [30]; whereas, other studies have reported associations between the short allele and ADHD and/or high impulsivity [9], [31]. Two recent meta-analyses conclude that there is no association between the 120-bp tandem and ADHD [28], [32]. In the current study, there were no significant differences in self-reported impulsive sensation seeking (nor for impulsivity and sensation seeking measured separately) between the 120-bp duplication alleles.…”
Section: Discussionmentioning
confidence: 99%